Future climate change under RCP emission scenarios with GISS ModelE2. (24th February 2015) - Nazarenko, L.; Schmidt, G. A.; Miller, R. L.; Tausnev, N.; Kelley, M.; Ruedy, R.; Russell, G. L.; Aleinov, I.; Bauer, M.; Bauer, S.; Bleck, R.; Canuto, V.; et al.
Abstract We examine the anthropogenically forced climate response for the 21st century representative concentration pathway (RCP) emission scenarios and their extensions for the period 2101–2500. The experiments were performed with ModelE2, a new version of the NASA Goddard Institute for Space Sciences (GISS) coupled general circulation model that includes three different versions for the atmospheric composition components: a noninteractive version (NINT) with prescribed composition and a tuned aerosol indirect effect (AIE), the TCAD version with fully interactive aerosols, whole‐atmosphere chemistry, and the tuned AIE, and the TCADI version which further includes a parameterized first indirect aerosol effect on clouds. Each atmospheric version is coupled to two different ocean general circulation models: the Russell ocean model (GISS‐E2‐R) and HYCOM (GISS‐E2‐H). By 2100, global mean warming in the RCP scenarios ranges from 1.0 to 4.5°C relative to 1850–1860 mean temperature in the historical simulations. In the RCP2.6 scenario, the surface warming in all simulations stays below a 2°C threshold at the end of the 21st century. For RCP8.5, the range is 3.5–4.5°C at 2100. Decadally averaged sea ice area changes are highly correlated to global mean surface air temperature anomalies and show steep declines in both hemispheres, with a larger sensitivity during winter months. By the year 2500, there are complete recoveries of the globally averaged surface air temperature for all versions of the GISS climate model in the low‐forcing scenario RCP2.6. TCADI simulations show enhanced warming due to greater sensitivity to CO2, aerosol effects, and greater methane feedbacks, and recovery is much slower in RCP2.6 than with the NINT and TCAD versions. All coupled models have decreases in the Atlantic overturning stream function by 2100. In RCP2.6, there is a complete recovery of the Atlantic overturning stream function by the year 2500 while with scenario RCP8.5, the E2‐R climate model produces a complete shutdown of deep water formation in the North Atlantic.